Developing a Congklak-Based Module to Enhance Early Childhood Number Recognition in the Independent Curriculum - Andi Hidayah Insani; Herlina Herlina; Sitti Nurhidayah Ilyas; Muhammad Yusri Bachtiar; Hajerah Hajerah; Rika Kurnia R (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Number recognition is a crucial component of early childhood cognitive development and is a key focus in the Independent Curriculum. Traditional teaching methods often struggle to fully engage young learners, highlighting the need for innovative, developmentally appropriate learning media. This study aimed to develop a Congklak-based learning module to enhance early childhood number recognition within the framework of the Independent Curriculum. Using a Research and Development (R&D) approach with the ADDIE model, which includes stages of analysis, design, development, implementation, and evaluation, this study involved 4 teachers and 30 children from Group B at TK Mansurin, Tarakan City. Data were collected through expert validation, teacher practicality questionnaires, and pre-test and post-test assessments of number recognition. Expert validation of the module indicated high validity with an average score of 92.43%, and teacher assessments revealed the module was highly practical with a score of 89%. The effectiveness of the module was analyzed using the Wilcoxon test, which demonstrated a statistically significant improvement in number recognition (p < 0.05). The average N-Gain of 0.68 confirmed the moduleÔÇÖs moderate effectiveness. The study concludes that the Congklak-based module is a valid, practical, and effective tool for enhancing early childhood number recognition within the Independent Curriculum, suggesting that traditional games can play a valuable role in modern educational settings.┬á┬áNumber recognition is a crucial component of early childhood cognitive development and is a key focus in the Independent Curriculum. Traditional teaching methods often struggle to fully engage young learners, highlighting the need for innovative, developmentally appropriate learning media. This study aimed to develop a Congklak-based learning module to enhance early childhood number recognition within the framework of the Independent Curriculum. Using a Research and Development (R&D) approach with the ADDIE model, which includes stages of analysis, design, development, implementation, and evaluation, this study involved 4 teachers and 30 children from Group B at TK Mansurin, Tarakan City. Data were collected through expert validation, teacher practicality questionnaires, and pre-test and post-test assessments of number recognition. Expert validation of the module indicated high validity with an average score of 92.43%, and teacher assessments revealed the module was highly practical with a score of 89%. The effectiveness of the module was analyzed using the Wilcoxon test, which demonstrated a statistically significant improvement in number recognition (p < 0.05). The average N-Gain of 0.68 confirmed the moduleÔÇÖs moderate effectiveness. The study concludes that the Congklak-based module is a valid, practical, and effective tool for enhancing early childhood number recognition within the Independent Curriculum, suggesting that traditional games can play a valuable role in modern educational settings.┬áKeywords: Congklak Game Module, Independent Curriculum, Number Recognition, Early Childhood Education